A validation framework to assess performance of commercial deformable image registration in lung radiotherapy. (July 2021) - Kumar, K.; Gulal, O.; Franich, R.D.; Kron, T.; Yeo, A.U.
Highlights: To provide a framework to objectively assess DIR in both high-/low-contrast areas. Used publicly available lung datasets and adjusted contrast levels before DIR. Velocity v4.1 DIR performance is a function of contrast level and extent of motion. Showed the need for multiple metrics to assess different aspects of DIR application. DIR assessment in low-contrast region is important for deformable dose accumulation. Abstract: Introduction: Deformable image registration (DIR) can play an important role in the context of adaptive radiotherapy. The AAPM Task Group 132 (TG-132) has described several quantitative measures for DIR error assessment but they can only be accurately defined when there is a ground-truth present in high-contrast regions. This work aims to set out a framework to obtain optimal results for CT-CT lung DIR in clinical setting for a commercially available system by quantifying the DIR performance in both low- and high-contrast regions. Methods: Five publicly available thorax datasets were used to assess the DIR quality. A "Ghost fiducial" method was implemented by windowing the contrast in a new feature provided by Varian Velocity v4.1. Target registration error (TRE) of the landmarks and Dice-similarity coefficient of the tumour were calculated at three different contrast settings to assess the algorithm in high- and low-contrast scenarios. Results: For the original unedited dataset, higher resolution DIR methods showed best performance acceptable within the recommended limit according to TG-132, when actual displacements were less than 10 mm. The relation of the actual displacement of the landmarks and TRE shows the limited capacity of the algorithm to deal with movements larger than 10 mm. Conclusion: This work found the performance of DIR methods and settings available in Varian Velocity v4.1 to be a function of contrast level as well as extent of motion. This highlights the need for multiple metrics to assess different aspects of DIR performance for various applications related to low-contrast and/or high-contrast regions.